Difference between revisions of "009C Sample Midterm 2, Problem 5"
Jump to navigation
Jump to search
Line 45: | Line 45: | ||
\displaystyle{\lim_{n\rightarrow \infty} \bigg| \frac{c_{n+1}x^{n+1}}{c_nx^n}\bigg|} & = & \displaystyle{\lim_{n\rightarrow \infty} \bigg|\frac{c_{n+1}x}{c_n}\bigg|}\\ | \displaystyle{\lim_{n\rightarrow \infty} \bigg| \frac{c_{n+1}x^{n+1}}{c_nx^n}\bigg|} & = & \displaystyle{\lim_{n\rightarrow \infty} \bigg|\frac{c_{n+1}x}{c_n}\bigg|}\\ | ||
&&\\ | &&\\ | ||
− | & = & \displaystyle{|x|\lim_{n\rightarrow \infty}\frac{c_{n+1}}{c_n}.} | + | & = & \displaystyle{|x|\lim_{n\rightarrow \infty}\bigg(\frac{c_{n+1}}{c_n}\bigg).} |
\end{array}</math> | \end{array}</math> | ||
|- | |- | ||
|Since the radius of convergence of the series <math style="vertical-align: -19px">\sum_{n=0}^\infty c_nx^n</math> is <math style="vertical-align: -5px">R,</math> we have | |Since the radius of convergence of the series <math style="vertical-align: -19px">\sum_{n=0}^\infty c_nx^n</math> is <math style="vertical-align: -5px">R,</math> we have | ||
|- | |- | ||
− | | <math>R=\frac{1}{\displaystyle{\lim_{n\rightarrow \infty} \frac{c_{n+1}}{c_n}}}.</math> | + | | <math>R=\frac{1}{\displaystyle{\lim_{n\rightarrow \infty} \bigg(\frac{c_{n+1}}{c_n}\bigg)}}.</math> |
|} | |} | ||
Line 63: | Line 63: | ||
\displaystyle{\lim_{n\rightarrow \infty} \bigg| \frac{c_{n+1}2^nx^{n+1}}{c_n2^{n+1}x^n}\bigg|} & = & \displaystyle{\lim_{n\rightarrow \infty} \bigg|\frac{c_{n+1}x}{2c_n}\bigg|}\\ | \displaystyle{\lim_{n\rightarrow \infty} \bigg| \frac{c_{n+1}2^nx^{n+1}}{c_n2^{n+1}x^n}\bigg|} & = & \displaystyle{\lim_{n\rightarrow \infty} \bigg|\frac{c_{n+1}x}{2c_n}\bigg|}\\ | ||
&&\\ | &&\\ | ||
− | & = & \displaystyle{\frac{|x|}{2}\lim_{n\rightarrow \infty}\frac{c_{n+1}}{c_n}.} | + | & = & \displaystyle{\frac{|x|}{2}\lim_{n\rightarrow \infty}\bigg(\frac{c_{n+1}}{c_n}\bigg).} |
\end{array}</math> | \end{array}</math> | ||
|- | |- | ||
|Hence, the radius of convergence of this power series is | |Hence, the radius of convergence of this power series is | ||
|- | |- | ||
− | | <math>\frac{2}{\displaystyle{\lim_{n\rightarrow \infty} \frac{c_{n+1}}{c_n}}}=2R.</math> | + | | <math>\frac{2}{\displaystyle{\lim_{n\rightarrow \infty} \bigg(\frac{c_{n+1}}{c_n}\bigg)}}=2R.</math> |
|- | |- | ||
|Therefore, this power series converges. | |Therefore, this power series converges. | ||
Line 89: | Line 89: | ||
\displaystyle{\lim_{n\rightarrow \infty} \bigg| \frac{c_{n+1}x^{n+1}}{c_nx^n}\bigg|} & = & \displaystyle{\lim_{n\rightarrow \infty} \bigg|\frac{c_{n+1}x}{c_n}\bigg|}\\ | \displaystyle{\lim_{n\rightarrow \infty} \bigg| \frac{c_{n+1}x^{n+1}}{c_nx^n}\bigg|} & = & \displaystyle{\lim_{n\rightarrow \infty} \bigg|\frac{c_{n+1}x}{c_n}\bigg|}\\ | ||
&&\\ | &&\\ | ||
− | & = & \displaystyle{|x|\lim_{n\rightarrow \infty}\frac{c_{n+1}}{c_n}.} | + | & = & \displaystyle{|x|\lim_{n\rightarrow \infty}\bigg(\frac{c_{n+1}}{c_n}\bigg).} |
\end{array}</math> | \end{array}</math> | ||
|- | |- | ||
|Since the radius of convergence of the series <math style="vertical-align: -19px">\sum_{n=0}^\infty c_nx^n</math> is <math style="vertical-align: -5px">R,</math> we have | |Since the radius of convergence of the series <math style="vertical-align: -19px">\sum_{n=0}^\infty c_nx^n</math> is <math style="vertical-align: -5px">R,</math> we have | ||
|- | |- | ||
− | | <math>R=\frac{1}{\displaystyle{\lim_{n\rightarrow \infty} \frac{c_{n+1}}{c_n}}}.</math> | + | | <math>R=\frac{1}{\displaystyle{\lim_{n\rightarrow \infty} \bigg(\frac{c_{n+1}}{c_n}\bigg)}}.</math> |
|} | |} | ||
Line 107: | Line 107: | ||
\displaystyle{\lim_{n\rightarrow \infty} \bigg| \frac{c_{n+1}(-x)^{n+1}}{c_n(-x)^n}\bigg|} & = & \displaystyle{\lim_{n\rightarrow \infty} \bigg|\frac{c_{n+1}(-x)}{c_n}\bigg|}\\ | \displaystyle{\lim_{n\rightarrow \infty} \bigg| \frac{c_{n+1}(-x)^{n+1}}{c_n(-x)^n}\bigg|} & = & \displaystyle{\lim_{n\rightarrow \infty} \bigg|\frac{c_{n+1}(-x)}{c_n}\bigg|}\\ | ||
&&\\ | &&\\ | ||
− | & = & \displaystyle{|x|\lim_{n\rightarrow \infty}\frac{c_{n+1}}{c_n}.} | + | & = & \displaystyle{|x|\lim_{n\rightarrow \infty}\bigg(\frac{c_{n+1}}{c_n}\bigg).} |
\end{array}</math> | \end{array}</math> | ||
|- | |- | ||
|Hence, the radius of convergence of this power series is | |Hence, the radius of convergence of this power series is | ||
|- | |- | ||
− | | <math>\frac{1}{\displaystyle{\lim_{n\rightarrow \infty} \frac{c_{n+1}}{c_n}}}=R.</math> | + | | <math>\frac{1}{\displaystyle{\lim_{n\rightarrow \infty} \bigg(\frac{c_{n+1}}{c_n}\bigg)}}=R.</math> |
|- | |- | ||
|Therefore, this power series converges. | |Therefore, this power series converges. |
Revision as of 12:46, 24 April 2017
If converges, does it follow that the following series converges?
(a)
(b)
Foundations: |
---|
Ratio Test |
Let be a series and |
Then, |
If the series is absolutely convergent. |
If the series is divergent. |
If the test is inconclusive. |
Solution:
(a)
Step 1: |
---|
Assume that the power series converges. |
Let be the radius of convergence of this power series. |
We can use the Ratio Test to find |
Using the Ratio Test, we have |
|
Since the radius of convergence of the series is we have |
Step 2: |
---|
Now, we use the Ratio Test to find the radius of convergence of the series |
Using the Ratio Test, we have |
Hence, the radius of convergence of this power series is |
Therefore, this power series converges. |
(b)
Step 1: |
---|
Assume that the power series converges. |
Let be the radius of convergence of this power series. |
We can use the Ratio Test to find |
Using the Ratio Test, we have |
|
Since the radius of convergence of the series is we have |
Step 2: |
---|
Now, we use the Ratio Test to find the radius of convergence of the series |
Using the Ratio Test, we have |
Hence, the radius of convergence of this power series is |
Therefore, this power series converges. |
Final Answer: |
---|
(a) converges |
(b) converges |